2009
DOI: 10.1007/s11605-009-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Anastomotic Repair in the Rat Intestine is Affected by Transient Preoperative Mesenteric Ischemia

Abstract: Introduction During bowel surgery, perioperative blood loss and hypotension can lead to transient intestinal ischemia. Recent preclinical studies reveal that the strength of intestinal anastomoses can be compromised after reperfusion. So far, this phenomenon has not been investigated in the very first days of healing when wound strength is lowest. Material and Method Ischemia was induced in rats by clamping both the superior mesenteric artery and ileal branches for 30 min. Immediately after declamping, anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…If a pressure of only 5 mmHg CO 2 was applied, this negative effect was not seen. Recent experimental work showed that ischemia-induced injury has greatest impact on intestinal anastomotic healing during the first 2 days after surgery [9]. In our study, a similar effect was still seen after a prolonged interval of 7 days.…”
Section: Discussionsupporting
confidence: 84%
“…If a pressure of only 5 mmHg CO 2 was applied, this negative effect was not seen. Recent experimental work showed that ischemia-induced injury has greatest impact on intestinal anastomotic healing during the first 2 days after surgery [9]. In our study, a similar effect was still seen after a prolonged interval of 7 days.…”
Section: Discussionsupporting
confidence: 84%
“…The identified risk factors for anastomotic leakage are composed of patient factors, which include malnutrition, weight loss, steroid use, smoking, alcohol, American Society of Anesthesiologists score > 3 points, various concurrent diseases such as cardiovascular disease and diverticulitis, and surgical factors, including a low level of anastomosis, an operation time > 2 hours, intraperitoneal fecal contamination, anastomotic tension, distal intestinal obstruction, and ischemia in the anastomosis [5]. Among these various causes of anastomotic leakage, ischemia around the anastomosis would be considered a strongly affective factor for repair of an anastomotic site [6, 7]. Several chemical agents have been introduced to attenuate ischemic injury to the colon, but their effect has not been promising, and there is a dearth of data regarding leakage prevention [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Small intestine and colonic anastomoses are simple to perform in rodents, as compared to esophagogastric anastomoses [15,16,17]. …”
Section: Discussionmentioning
confidence: 99%